CUSTOMIZATION AND USABILITY TESTING AUTO ESSAY FILE GRADING LMS BASED METACOGNITIVE ASSESSMENT IN ENGINEERING FACULTY - Ridwan Daud Mahande; Jasruddin; Fitrah Asma Darmawan; Muhammad Ayat Hidayat (Informatika, Universitas Jenderal Soedirman, 2022)
Online learning assessment and evaluation has been widely used using the Learning Management system (LMS). However, the form of the questions is still based on multiple choice. Evaluation and form of questions in LMS need to be developed by exploring metacognitive thinking. The LMS plugin supports Essay-based questions and assessments, it's just that this plugin needs to be supported with file submissions and metacognitive assessment rubrics. Therefore, this research aims to customize and test the usability of Auto Essay File Grading (AEG) metacognitive assessment based on LMS. This study uses a quantitative descriptive approach conducted at the Faculty of Engineering, Universitas Negeri Makassar, with lecturers and students as respondents. Data were collected through the USE questionnaire and analyzed using descriptive statistics. The results of the analysis of AEG usability testing from the point of view of lecturers and students who have the highest average are a usefulness. For the lowest average of the lecturers is the ease of use and from the student, the side is the ease of learning. These results also prove that the AEG application/plugin needs improvement in terms of ease and practicality of use so that users learn how to use it faster. Recommendations for ease of use and learning are discussed and explained further, along with the improved display, answer keywords, and minimizing irrelevant menus.